Synthesis of high value chemicals from biomass platform chemicals - Koh, Jackson Peng Fei (2016)
In this thesis, the conversion of biomass to several high value chemicals via versatile and synthetically useful platform chemicals was described. These high value chemicals include a common intermediate that allow access to several potent NK1 receptor antagonists which are associated with the treatment of anxiety and emesis, as well as biologically active natural products aspergillides A and B with cytotoxic activity against mouse lymphocytic leukemia cell (L1210). In particular, the syntheses of aspergillides A and B was achieved such that all of the carbons present are derived from biomass derived platform chemicals. These demonstrate the feasibility of constructing valuable biologically active compounds using a sustainable chemical feedstock like biomass.